Focus Questions for Philosophy 167: Class 4. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Assignment for September 23 Kepler's Planetary System and the Rudolphine Tables.; Readings and 5 focus questions.